Investigation of Anti-Carcinogenic Properties of 2-(2,3,4-trimethoxyphenyl)-1-(substituephenyl) Acrylonitrile and 7,8-dihydroxy-1-(substituephenyl) Coumarine Compounds against Human Breast Cancer Cell Lines - Tekin, Suat; Koran, Kenan; Ozen, Furkan; Gorgulu, Ahmet Orhan; Sandal, Suleyman (Wiley, 2015)
[Abstract Not Available]